Starch modification using green technologies - Lima, Dâmaris Carvalho (2021)
Starches are widely used in different industries and products, due to their diverse properties. However native starches may not present some particular properties required for industrial use. In order to overcome limitations, the modification of starch is an alternative to improve their performance. However, most of starch modification methods used by the industry generate wastes that must be adequately treated to do not compromise the environment nor food. Therefore, alternatives to meet the industries\' necessities without generating toxic residues are needed. In this context, it is important to study emerging \"environmentally friendly\" technologies, also called \"green technologies\", such as ozone (O3) and dry heating treatments (DHT). This PhD Thesis is divided in five chapters: The first chapter contextualize this work, comprising Introduction and Thesis Organization, Objectives and Literature Review sections. Then, the ozonation process was evaluated in two starch sources: cassava (Chapter 2) and arracacha (Chapter 3). These chapters demonstrated the ozone treatment was able to form carbonyl and carboxyl groups, as well as to cause changes in the molecular size distribution (depolymerization), which affected and changed both cassava and arracacha starches properties. Some highlighted results with potential application are: reduction of the paste apparent viscosity, reduction of the starch retrogradation, stronger hydrogels (in special at acid conditions), and higher paste clarity. Then, in Chapter 4, the cassava starch was modified by using the combination of both O3 and DHT treatments. The combination of treatments promoted different modifications concerning the single treatments. Furthermore, the sequence of these treatments influenced many properties of the obtained modified starch. For instance, the samples that were modified with the sequence combination of DHT with O3 (DHT+ O3) showed the highest degree of oxidation, and a gel more resistant to break than the other hydrogels. On the other side, the starch modified with the opposite sequence (O3+DHT) exhibited a degree of oxidation similar to O3 starch, a molecular size distribution with very small-sized molecules, and capacity to form weaker gels than the native. Finally, the last part of the Thesis (Chapter 5) comprising the General Conclusions and Suggestions for Future Research sections. Therefore, the relevance of the present Thesis is based on the in-depth study of the ozonation process, as well as the novel proposal of combining ozone and DHT treatments, focusing on discuss \"green\" alternatives for starch modification.